1999
DOI: 10.1002/(sici)1097-0339(199905)20:5<271::aid-dc5>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Logistic regression analysis of small round cell neoplasms: A cytologic study

Abstract: The diagnosis of small round cell neoplasms (SRCN) in children is difficult by both histologic and cytologic methods. These neoplasms are unified morphologically by the scanty cytoplasm surrounding relatively round nuclei containing a primitive chromatin pattern. Further categorization is achieved histologically by the recognition of architectural differentiation and cytoplasmic features. Numerous series and case reports documenting the cytologic features of SRCN have been published in the English‐language lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…ES/PNETs are typically highly cellular smears with many small round single cells with focal cell clustering, high nuclear-cytoplasmic ratios, scanty indistinct cytoplasm, round to oval nuclei with finely stippled nuclear chromatin, and small or absent nucleoli. 4,5,8,9,21,[33][34][35] In some cases, focal nuclear molding is present, and glycogen-laden cytoplasmic vacuoles are visible on a Diff-Quik stain. 4,5,8,9,21,[33][34][35] Lymphoglandular bodies 8,33 and ganglion-like cells are not seen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ES/PNETs are typically highly cellular smears with many small round single cells with focal cell clustering, high nuclear-cytoplasmic ratios, scanty indistinct cytoplasm, round to oval nuclei with finely stippled nuclear chromatin, and small or absent nucleoli. 4,5,8,9,21,[33][34][35] In some cases, focal nuclear molding is present, and glycogen-laden cytoplasmic vacuoles are visible on a Diff-Quik stain. 4,5,8,9,21,[33][34][35] Lymphoglandular bodies 8,33 and ganglion-like cells are not seen.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 -6 Other malignancies that are considered in the SRCT differential diagnosis include blastemal-type Wilms tumor, desmoplastic small-cell tumor of the peritoneum, small-cell variant of synovial sarcoma, small-cell osteogenic sarcoma, undifferentiated (anaplastic) hepatoblastoma, Merkel-cell carcinomas, metastatic smallcell carcinomas, and granulocytic sarcomas. [1][2][3][4][5][6][7][8][9][10][11] As several studies have reported, fine-needle aspirate (FNA) has become an important modality of diagnosis for these SRCTs. 2,5,12 The use of ancillary studies has proven to be a decisive step in FNA diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[33738] The presence of strap or tadpole cells is deemed to be strongly associated with rhabdomyosarcoma. [57] The finding of cells with more abundant cytoplasm, eccentrically located nuclei, and bi/multinucleated tumor cells in a background of mucosubstance helps to distinguish RMS from other small round cell tumors. [3940]…”
Section: Rhabdomyosarcomamentioning
confidence: 99%
“…[3] As seen in several study reports, fine needle aspiration cytology (FNAC) has become an important modality of diagnosis for these tumors. [45] It yields adequate numbers of dissociated, viable cells making it ideally suitable for ancillary techniques.…”
Section: Introductionmentioning
confidence: 99%